2021
DOI: 10.3390/catal11091078
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Pd/C-Catalyzed Reactions

Abstract: The Pd/C-catalyzed reactions, including reduction reactions and cross-coupling reactions, play an irreplaceable role in modern organic synthesis. Compared to the homogeneous palladium catalyst system, the heterogeneous Pd/C catalyst system offers an alternative protocol that has particular advantages and applications. Herein, a review on Pd/C-catalyzed reactions is presented. Both the advances in Pd/C-catalyzed methodologies and the application of Pd/C-catalysis in total synthesis are covered in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…The tetrahydrophenanthren‐4(1 H )‐ones with various functional groups were converted to the hexahydrophenanthren‐4(1 H )‐one through catalytic hydrogenation [21] . The hexahydrophenan‐threne skeleton is similar to a known precusor of lepenine, which could be synthesized from our products 8 a – e [22] .…”
Section: Resultsmentioning
confidence: 98%
“…The tetrahydrophenanthren‐4(1 H )‐ones with various functional groups were converted to the hexahydrophenanthren‐4(1 H )‐one through catalytic hydrogenation [21] . The hexahydrophenan‐threne skeleton is similar to a known precusor of lepenine, which could be synthesized from our products 8 a – e [22] .…”
Section: Resultsmentioning
confidence: 98%
“…5 has a special place in organic synthesis and transfer hydrogenation of various reducible functional groups. 13 Also, Pd/C has been used to eliminate bromate in water, 14 N-formylation of amines, 15 Stille 16 and Suzuki 17 couplings, and aerobic esterication of alcohols. 18 Pd/C NPs are widely used in nitro reduction in the presence of various H-sources, that could point to some examples: (1) Pd/ C with ammonium formate or hydrazine hydrate, 6,19 (2) Pd-C with polymer-supported formate, 2 (3) Pd/C with ammonium formate/silica, 20 (4) CoFe 2 O 4 @Pd/activated carbon nanocomposite/NaBH 4 , 21 and (5) Pd/CNS (carbon nanospheres) under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Palladium supported on carbon (Pd/C) has a special place in organic synthesis and transfer hydrogenation of various reducible functional groups. 13 Also, Pd/C has been used to eliminate bromate in water, 14 N -formylation of amines, 15 Stille 16 and Suzuki 17 couplings, and aerobic esterification of alcohols. 18…”
Section: Introductionmentioning
confidence: 99%
“…Biaryl and heteroaryl are fundamental units of numerous natural products and advanced functional materials [ 15 ]. Palladium-catalyzed Suzuki–Miyaura (S–M) cross-coupling reaction has been recognized as one of the most effective methods for preparing biaryl and heteroaryl compounds [ 16 , 17 , 18 , 19 ]. Over the past decade, some research results demonstrated that S–M reactions could be carried out by treated plant materials and bio-wastes, which bear the features of eco-friendliness, cost-effectiveness, and safety.…”
Section: Introductionmentioning
confidence: 99%